Transgenerational Plasticity in Flower Color Induced by Caterpillars - Sobral, Mar; Neylan, Isabelle P.; Narbona, Eduardo; Dirzo, Rodolfo (Frontiers in Plant Science, 2021)
Variation in flower colour due to transgenerational plasticity could stem directly from abiotic or biotic environmental conditions. Finding a link between biotic ecological interactions across generations and plasticity in flower colour would indicate that transgenerational effects of ecological interactions, such as herbivory, might be involved in flower colour evolution. We conducted controlled experiments across four generations of wild radish (Raphanus sativus, Brassicaceae) plants to explore whether flower colour is influenced by herbivory, and to determine whether flower colour is associated with transgenerational chromatin modifications. We found transgenerational effects of herbivory on flower colour, partly related to chromatin modifications. Given the presence of herbivory in plant populations worldwide, our results are of broad significance and contribute to our understanding of flower colour evolution.